Enhanced specific capacity and cycle stability of hybrid supercapacitors using carbonized polyphosphazene-based nanocomposites. (20th November 2021) - Zhang, Xiaoyan; He, Shufu; Wo, Xinxing; Han, Tongwei; Kambonde, Jerricia A.N.N.; Wu, Jingbo; Qiu, Xinping; Zhao, Long
Highlights: Carbonized PZS microspheres was fabricated as electrodes in asymmetric hybrid supercapacitors. The negative PZSC exhibited a specific capacitance of 193.2 F g −1 with no loss after 10000 cycles. The positive Ag NWs @ PZSC performed greater specific capacity and cycle stability than Ag NWs. The assembled cell showed good specific capacity (34.05 mA h g −1 ) and cycle stability (92.11%). Abstract: This work aims to explore the utility of the polyphosphazene-based nanomaterials as both negative and positive heteroatom-doped porous carbon materials in hybrid supercapacitors. To this end, carbonized Poly (hexachlorocyclotriphosphazene-co-bisphenol S) (PZS) microspheres at different temperatures were employed as negative materials and carbonized Ag nanowires/PZS nanocomposites (Ag NWs @ PZSC) were used as positive materials. The carbonized PZS microspheres at 900 o C (PZSC900) exhibited a lager surface area with more micropores than PZSC700 and PZSC800, endowing the former with a distinguished specific capacitance (193.2 F g −1 ) and an outstanding cycle stability (nearly 100% after 10000 cycles). The Ag NWs @ PZSC with an amorphous carbon coating layer outperforms the Ag NWs, reaching a specific capacity of 113.33 mAh g −1 . Importantly, the optimized negative and positive materials were rationally assembled to an asymmetric cell in an alkaline aqueous electrolyte, which exhibited a cell specific capacitance of 76.6 F g −1 and a cycle stability of 92.11% after 10000 cycles. The findings demonstrate that PZS is a promising precursor for constructing high-performance hybrid supercapacitors. Graphical abstract: Image, graphical abstract